UJI KANDUNGAN FENOLIK TOTAL DAN AKTIVITAS ANTIBAKTERI EKSTRAK KULIT BUAH ASAM PAYA (Eleiodoxa conferta (Griff.) Burret) TERHADAP Staphylococcus aureus. - Elisabeth SITORUS, Febrina Claudia; Dwi WULANSARI, Endang; SULISTYARINI, Indah (Media Farmasi Indonesia, 2020)
Asam paya (Eleiodoxa conferta (Griff.) Burret) contains phenolic compounds which can function as antibacterial agents against Staphylococcus aureus. Extraction using soxhlet with multilevel polarity, namely n-hexane and ethanol. The antibacterial activity test by TLC contact-bioautography showed that the phenolic compounds in the ethanol extract had antibacterial activity, and the diffusion test results showed that the ethanol extract had a larger inhibition zone diameter than the n-hexane extract. The total phenolic compound of extract was determined using the Folin-Ciocalteu reagent. The total phenolic compounds of Eleiodoxa conferta (Griff.) Burret. ethanolic extract is 7,326± 0,0989 mg GAE/gram sample. The ethanol extract was fractionated using a separating funnel, followed by purification with preparative TLC. The phenolic isolates obtained were tested for purity by three eluent TLC. The results of antibacterial activity diffution test and TLC contact-bioautography test showed that phenolic isolates had antibacterial activity against Staphylococcus aureus.